Regularity effects in word naming: what are they? - Cortese, Michael J.; Simpson, Greg B. (Memory & Cognition, 2000)
In a word-naming experiment, word-body consistency was crossed with grapheme-to-phoneme regularity to test predictions of current models of word recognition. In the latency and error data, a clear effect of consistency was observed, with the influence of regularity somewhat weaker. In addition, simulation data from three contemporary models of word recognition were obtained for the stimuli used in the experiment in order to compare the models' latencies with those of humans. The simulations showed that the human latency data are most consistent with the parallel-distributed-processing model of Plaut, McClelland, Seidenberg, and Patterson (1996), less so with the dual-process model (Zorzi, Houghton, & Butterworth, 1998), and least so with the dual-route-cascaded model (Coltheart & Rastle, 1994). Reprinted by permission of the publisher.